The perception of institutions supporting families from the perspective of the experience of today’s Polish and foreign prisoners - Urbanek, Arkadiusz (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2014)
Reflections over the role of institutions dealing with pathological families have been always of great importance for pedagogical sciences. Such dysfunctional features are typical for the majority of those families from which today's prisoners come from, particularly re-offenders. Hence, the question arising about the role of the institutions in inhabiting the deprivation process among children upon their socialization, with the theoretical and practical implications of such activities. Therefore, the discourse embraces the issues of inclusion and exclusion as bipolar perspectives of intervention, nursing and resocialisational activities. Reflections undertaken from such angles consider the role of external institutions in the lives of today’s prisoners. The interviews carried out with Polish as well as foreign recidivist prisoners have been analyzed on the basis of the reconstruction of their socialisation that took place in the 1970s, 1980s and 1990s, in different cultural conditions and society organisation. The aim of the research was to capture the role of the institutions supporting families from the perspective of the respondents’ experience, regardless of their social background.
Keywords: prison; socialization; institutions; interculturalism